LINGKUNGAN KERJA FISIK, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KELURAHAN TITIPAPAN KECAMATAN MEDAN DELI - Ella Ardila; Sinto Sinto; Eka Umi Kalsum (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2023)
Physical Work Environment, Work Discipline and Job Satisfaction with Employee Performance at the Titipapan Medan Deli Village Office, Journal 2021. The existence of this study aims to find the relationship in the Titipapan Medan Deli Village Office to Employee Performance in the Physical Work Environment, Work Discipline and Job Satisfaction. The data analysis method uses quantitative data analysis, the primary data type and the multiple linear analysis method.This was analyzed through observation, questionnaire distribution and interviews. The respondents who became the sample consisted of 30 people. The results of this study show simultaneously that Physical Work Environment (X1), Work Discipline (X2) and Job Satisfaction (X3) have a positive and significant effect on Performance (Y).